PD1/PD-L1 pathway in psoriasis and psoriatic arthritis: a review - Adamczyk, Michał; Krasowska, Dorota (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2021)
Programmed-death 1 (PD-1) is a co-receptor that inhibits the inflammatory response, and thus helps in maintenance of peripheral immunotolerance. Impairment in the PD-1/PD-L1 pathway is believed to play an important role in many immune-mediated diseases, including systemic lupus erythematosus, rheumatoid arthritis, systemic sclerosis and autoimmune hepatitis, and, as emphasized recently, in psoriasis and psoriatic arthritis. Biologic drugs targeting immune checkpoint regulators may be associated with new-onset psoriasis or exacerbations of pre-existing dermatosis. In this review we discuss the role of PD-1/PD-L1 pathway in psoriasis basing on data published to date.